ANALISIS FAKTOR PENYEBAB TINDAK KORUPSI PUNGUTAN LIAR OLEH KEPALA DESA TAMBUSAI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR TAHUN 2020 - Safitri, Nur Ihdatia; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Corruption from a government perspective is the abuse of public power for personal or group gain. This includes various forms of action such as bribery, extortion, fraud, and nepotism. Corruption undermines public trust in government institutions, hinders economic development, and exacerbates social injustice. This research aims to analyze the factors that cause illegal levies of corruption by the Head of Tambusai Village, Rumbio Jaya District, Kampar Regency in 2020. The method used in this research is a qualitative method, with descriptive research type and the research location is in Tambusai Village, Kampar Regency, the type of data used is primary and secondary data, and the data collection techniques used are interviews and documents. The data analysis technique used is searching or collecting data, describing, analyzing and then concluding. The findings obtained in this research are that there are several factors that cause corruption or illegal levies carried out by the Tambusai Village Head, namely personal greed, opportunity, then unmet needs, resulting in disclosure. Keywords: Greed, opportunity, need for disclosure, illegal levies